The Lower Limb Assessment Score: A valid measure of hypermobility in elite football?. (May 2019) - Paul Johnson, Adam; Ward, Sarah; Simmonds, Jane
Abstract: Objective: This study aims to validate the Lower Limb Assessment Score against the current gold standard Beighton Scale within an adult elite footballing population to allow for future research to explore the influence of lower limb specific hypermobility on injury incidence. Design: Observational cohort study. Setting: Thirty-six male, professional footballers aged between 18 and 37 years old. Main outcome measures: The Sensitivity, specificity, positive predictive value, negative predictive value and Spearman's rank correlation between the LLAS and Beighton Scale. Results: There was significant strong correlation between LLAS and Beighton Scale scores ( ρ  = 0.732; p < 0.001). The LLAS displayed a sensitivity of 67% and specificity of 94% when a cut off of ≥4/12 was applied to the screening data. This cut off point also yielded moderate Positive Predictive Validity (50%) and excellent Negative Predictive Validity (97%). Conclusions: The present study suggests that the LLAS is a valid test for identifying lower limb hypermobility within an adult male footballing population when a cut off of ≥4/12 is used. Highlights: The LLAS has excellent specificity in lower limb GJH screening in elite footballers. The LLAS appears to be a valid test for GJH with a cut off of ≥4/12. The LLAS could be utilised to understand the influence of lower limb specific joint hypermobility on injury rates.